Maps of wind hazard over South Eastern South America considering climate change - Sanabria, L. Augusto (2018)
Wind is one of the most dangerous natural phenomena for the built environment in South Eastern South America. The hazard posed by wind depends on the extreme wind speeds on the surface and can be quantified by calculating the Average Recurrence Interval—more commonly known as return period—of these winds. Maps of return period of extreme wind speeds are used by planning authorities to enforce appropriate standards for infrastructure construction in most countries of the world. These maps are usually built up from wind speeds recorded at a network of weather stations. In some countries, however, the quality of the records is poor or the stations have not been in operation for long enough to give appropriate data for wind hazard studies. In this paper, we discuss an alternative approach based on wind speeds calculated by climate models. The approach provides longer datasets and facilitates assessment of the impact of climate change on wind hazard, a matter of great of importance for planning and emergency authorities. Map quality is evaluated by comparing results from the climate simulations with results from reanalysis. The comparison shows that the climate simulations produce results close enough to the reanalysis and hence they can be used for wind hazard assessment. The results also show that we could expect little variation in wind hazard in South Eastern South America during most of this century.